Genetica del color del pelaje en el cruce R1 ( Cebu x F1 Holstein/Cebu) - Berovides, V.
(En, Es)
Ilus., 8 ref.
Keywords: GANADO BOVINO; GENETICA; COLOR; PELO; GENES; LOCI; CRUZAMIENTO; CEBU; CUBA; RAZA HOLSTEIN; REVISTA DE SALUD ANIMAL